Factors Influencing Nursing Student's Satisfaction in the Clinical Practice Education Program: A Systematic Review - Arief Wahyudi Jadmiko; Estivana Felaza (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Nursing education programs' major success is arguably linked to students' practical clinical practice. The practical clinical practice provides a realistic setting in which students can safely integrate theoretical nursing knowledge into practical nursing care while also developing the attitudes and abilities required for the profession. This study aimed to examine the factors influencing nursing students' satisfaction in the clinical practice education program.Subjects and Method: A systematic review were conducted by searching articles from PubMed, ResearchGate, Science Direct, Google Scholar, and EBSCO is an article published from 2012 to 2022. The keywords were “clinical practice” AND “education” AND “students, nursing” AND “satisfaction”. The inclusion criteria were cross-sectional study. The articles were selected by PRISMA flow diagram.Results: A total of 8 studies was included in this review. Individualized supervision model, the pedagogical atmosphere on the ward, the relationship with the clinical nurse supervisors, the relationship with the nurse teachers, leadership style, clinical nurse commitment, patient relationships, higher age, grade point average (GPA), completion of several clinical courses, type of service and center, the type of management, the preference in the choice of the practice center, the number of students per period per clinical educator, being a woman and being in the second-grade year group, unhealthy placement environments.Conclusion: Factors influencing the satisfaction of student nurses in the clinical practice education program are the type of management, service, and center; the premises of nursing in the ward; the pedagogical atmosphere on the ward; the Ward/ Nurse Manager’s leadership style; individualized supervision model; unhealthy placement environments, clinical tutors and nurse teacher.Keywords: clinical practice, learning, education, students, nursing, satisfaction.Correspondence: Arief Wahyudi Jadmiko. Nursing Department, Faculty of Health, Universitas Pembangunan Nasional Veteran Jakarta. Jl. RS. Fatmawati Raya, Pd. Labu, Cilandak, Depok, West Java. Email: ariefwjadmiko@gmail.com. Mobile: +62 856-4721-3628.Indonesian Journal of Medicine (2023), 08(02): 225-235https://doi.org/10.26911/theijmed.2023.08.02.12